The factors affecting academic burnout in medical students of Mashahd University of Medical Sciences in 2013-2015 - Shokrpour, Nasrin (J Educ Health Promot, 2020)
INTRODUCTION: Academic burnout is one of the issues involving the educational systems at all levels, which wastes the human resources and expenditures. Academic burnout refers to the sense of exhaustion due to educational requirements, the sense of cynicism and indifference, and the sense of lack of competence. Considering the fact that burnout has already been studied in different professions and in cultures different from that of ours, there is a need to identify these factors among the Iranian medical students and accordingly propose some strategies to reduce burnout symptoms among these students. With this end, this study aimed to identify and quantify the importance of possible factors causing burnout among medical students in the 2(nd) and 4(th) years of their studies in Mashahd University of Medical Sciences and provide some suggestions. METHODS: The present research is a cross-sectional study conducted in 2017. The participants included medical students who had entered Mashhad University of Medical Sciences in Iran in 2013 and 2015 and were in their 4(th) and 2(nd) year of their studies in the university. A questionnaire prepared and validated by Maslach et al. was used to collect the data and distributed among 195 participants who were selected randomly as the sample. RESULTS: The results showed that the mean scores given by 195 selected respondents regarding emotional exhaustion, indifference, and inefficiency were respectively 3.89, 3.87 and 4.12 out of 7. CONCLUSION: Based on the results, students had the highest level of academic burnout in personal inefficiency or incompetence component and the lowest level was observed in indifference. Therefore, burnout and its components were explicitly seen among medical students; the authorities are recommended to take measures to reduce academic burnout among the students.